2009
DOI: 10.1002/pmic.200900269
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein glycation using phenylboronate acrylamide gel electrophoresis

Abstract: The incorporation of the specialized carbohydrate affinity ligand methacrylamido phenylboronic acid in polyacrylamide gels for SDS-PAGE analysis has been successful for the separation of carbohydrates and has here been adapted for the analysis of post-translationally modified proteins. While conventional SDS-PAGE analysis cannot distinguish between glycated and unglycated proteins, methacrylamido phenylboronate acrylamide gel electrophoresis (mP-AGE) in low loading shows dramatic retention of delta-gluconolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 48 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…The Flu-PAGE results observed with saccharide-incubated serum samples are consistent with those found when analysing HSA glycation using mP-AGE19, showing strongest interactions between boronic acid and cis -1,2-diol-containing fructosamine adducts (resulting from glycation with glucose, mannose and galactose), stabilised by an electrostatic interaction between the protonated amino group and the negatively charged boronate moiety. When using Flu-PAGE in conjunction with mP-AGE analysis of the serum sample, the highest fluorescence intensity can be observed in the glycated HSA fraction that is retained in its electrophoretic mobility via interaction with the gel-incorporated MPBA (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The Flu-PAGE results observed with saccharide-incubated serum samples are consistent with those found when analysing HSA glycation using mP-AGE19, showing strongest interactions between boronic acid and cis -1,2-diol-containing fructosamine adducts (resulting from glycation with glucose, mannose and galactose), stabilised by an electrostatic interaction between the protonated amino group and the negatively charged boronate moiety. When using Flu-PAGE in conjunction with mP-AGE analysis of the serum sample, the highest fluorescence intensity can be observed in the glycated HSA fraction that is retained in its electrophoretic mobility via interaction with the gel-incorporated MPBA (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 83%
“…We first tested this technique on simple carbohydrates and showed that by using the same basic principle as BAC, exploiting the reversible covalent interaction between boronic acid and cis -diols1718, the MPBA-incorporated acrylamide gels enabled the improved separation of saccharides, and the differentiation between monosaccharides and dissacharides. Later we adapted this boronate-assisted saccharide electrophoresis (BASE) method to allow the separation of glycated from non-glycated proteins by incorporating MPBA into polyacrylamide gels for sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) analysis1920. This method, coined mP-AGE, showed that under electrophoresis conditions the polyacrylamide incorporated MPBA is specific for fructosamine modified proteins, via interactions with the cis -1,2-diol-containing fructosamine adducts and by further stabilisation through an electrostatic interaction between the protonated amino group and the negatively charged boronate moiety19.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One current clinical assay based on an enzymatic method utilizes an albumin-specific proteinase (i.e., ketoamine oxidase) to digest glycated HSA, followed by treatment with a fructosaminase to oxidize the glycated amino acids and produce hydrogen peroxide, which is then measured [59–61]. Raman spectroscopy [63], refractive index measurements [64], capillary electrophoresis [65] and other electrophoretic methods [66,67] have also been explored as alternative techniques for measuring glycated albumin.…”
Section: Measurement Of Glycated Albuminmentioning
confidence: 99%
“…Since albumin is the most abundant protein in P/S, fructosamine is predominantly a measure of GA—though other circulating proteins such as glycated lipoproteins and glycated globulins do contribute to the total concentration of fructosamine [25]. The concentration of GA can be directly measured by several methods, including gel electrophoresis, enzymatic methods, colorimetry, and immunoassays [18, 19, 26, 27]. HbA1c remains the primary test for protein glycation that is used to monitor diabetes; however, studies have shown that GA may be more reliable than HbA1c in certain instances—such as specific clinical conditions in which HbA1c does not work properly (e.g., iron deficiency, pregnancy, and end-stage renal disease) [28].…”
Section: Introductionmentioning
confidence: 99%